2006
DOI: 10.1111/j.1440-1819.2006.01505.x
|View full text |Cite
|
Sign up to set email alerts
|

Egalitarian sex role attitudes among Japanese human service professionals: Confirmatory factor analytic study

Abstract: The psychometric properties of the short form of the Scale of Egalitarian Sex Role Attitudes (SESRA-S) were studied among human service professionals. An exploratory factor analysis yielded two factors interpreted as reflecting women's rights (e.g. women at home and men at work [a reverse item]) and women's independence (e.g. working outside is equally important for women [a non-reverse item]), respectively. Confirmatory factor analysis showed a good fit. Impact of participant age, sex, residential area, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
(39 reference statements)
1
12
0
Order By: Relevance
“…These roles refer to what we have described in the introduction as formal contact egalitarianism which as was pointed out tends to be associated with the public social sphere which appears to be more progressive than the private social sphere. This result is consistent with similar findings reported by Uji et al (2006) and can be attributed to the fact that in Greece rural areas on the whole tend to be closer to traditional forms and structures (Argyrou 1996).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…These roles refer to what we have described in the introduction as formal contact egalitarianism which as was pointed out tends to be associated with the public social sphere which appears to be more progressive than the private social sphere. This result is consistent with similar findings reported by Uji et al (2006) and can be attributed to the fact that in Greece rural areas on the whole tend to be closer to traditional forms and structures (Argyrou 1996).…”
Section: Discussionsupporting
confidence: 95%
“…Uji et al (2006) have found that people who live in rural areas had less egalitarian attitudes than people who reside in urban areas. Based on the above finding, we wanted to see whether the same results will be revealed from the Greek sample having in mind Argyrou's (1996) ethnographic study which indicated a similar point.…”
Section: Introductionmentioning
confidence: 96%
“…There were three latent variables: Rape Myth Acceptance, a factor that was abstracted from the RMS‐S; and two subscales of the SESRA‐S: Women's Rights and Women's Independence. Furthermore, we presumed a correlation between Women's Rights and Women's Independence because an exploratory factor analysis produced a correlation between these two factors of 0.312 36 . The fitness of this model was as follows: GFI (0.850), AGFI (0.821) and RMSEA (0.074).…”
Section: Resultsmentioning
confidence: 99%
“…Uji et al . conducted exploratory factor analysis of the SESRA‐S and found two factors of the inventory 36 . The description of the items belonging to the first factor generally addresses the idea that women are supposed to take traditional women's role.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation